Treatment Outcome of Tennis Elbow by Percutaneous Needle Tenotomy - Kayatha, Nirab; Joshi, Amit; Chand, Pankaj; Thapa, Bishnu Babu; Rana, Sushil; Singh, Bharat Prasad; KC, Bachhu Ram; Shah, Bhanu Chandra (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Tennis elbow (TE), or lateral epicondylitis of the humerus, is a painful condition seen commonly in the daily practice of Orthopaedic surgeons. One of the myriad of treatment methods for TE is percutaneous needle tenotomy of the common extensor origin. It is a simple operation with minimal morbidity and good-to-excellent results in most of the patients. The aim of this study was to evaluate the outcome in patients with chronic TE. Methods: this was a prospective study in 33 consecutive patients of both sexes with TE who were above 30 years of age. An 18 Gauge hypodermic needle was used under local anaesthesia to percutaneously tenotomise the extensor origin at the point of maximum tenderness. Visual analogue score (VAS) was used to assess the pain prior to intervention and in subsequent follow-ups at first, third, sixth and 12th weeks. Persistence of pain and return to activities of the patients was used to evaluate outcome as excellent, good, fair or poor. Results: At the end of 12 weeks, eleven out of 30 elbows (36.7%) had an excellent outcome, 13 (43.3%) had good, 5 (16.7%) had fair and 1 patient (3.3%) had poor outcome. At first week follow-up, the mean pain at rest was 4.60, the same at night was 2.73 and activity pain was a mean of 7.70 (max-9, min-5). By 12 week follow-up, the mean VAS scores at rest, night and activites were 0.87, 0.63 and 1.53 respectively, showing significant decrease in pain. Conclusions:Percutaneous tenotomy is a simple, safe, patient friendly, effective and easily reproducible method of treating tennis elbow. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/32-35 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7907